2020
DOI: 10.1177/0091415020957387
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Depression Scale (GDS-15): Validation in Mexico and Disorder in the State of Knowledge

Abstract: The objective of this study was to evaluate the reliability and validity of the Geriatric Depression Scale in its 15-item version (GDS-15) in Mexican older adults. Participants included 1178 older adults between the ages of 60 and 94 ( M = 69.16, SD = 7.69); 53.9% were women and 55.8% were married or with a partner. They completed the GDS-15, a subjective well-being scale, and a quality-of-life questionnaire. A Kuder–Richardson coefficient of .80 was obtained, which indicates an acceptable internal consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…The composite scores of memory (ADNI‐MEM) and executive function (ADNI‐EF) were generated by the ADNI neuropsychological battery to reflect memory and executive functions, respectively 16 . The 15‐item Geriatric Depression Scale (GDS‐15) was used to assess depressive symptoms 17 . In studies using the GDS‐15 to assess depressive symptoms in older adults, scores higher than 5 indicated the presence of clinical depression 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The composite scores of memory (ADNI‐MEM) and executive function (ADNI‐EF) were generated by the ADNI neuropsychological battery to reflect memory and executive functions, respectively 16 . The 15‐item Geriatric Depression Scale (GDS‐15) was used to assess depressive symptoms 17 . In studies using the GDS‐15 to assess depressive symptoms in older adults, scores higher than 5 indicated the presence of clinical depression 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The MAS study examined the prevalence of MCI and psychological and behavioral symptoms in the nondemented older population (Sachdev et al, 2010). Studies suggest that GDS-15 is not suitable for people with cognitive and communication difficulties (Azulai & Walsh, 2015), and the reliability of GDS-15 test scores varies with impaired cognitive functioning (Acosta Quiroz et al, 2021). However, the validation studies of GDS-15 demonstrated it to be a valid tool in nondemented populations and people with MCI making it an appropriate tool for the MAS study (Nyunt et al, 2009; Acosta Quiroz et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Studies suggest that GDS-15 is not suitable for people with cognitive and communication difficulties (Azulai & Walsh, 2015), and the reliability of GDS-15 test scores varies with impaired cognitive functioning (Acosta Quiroz et al, 2021). However, the validation studies of GDS-15 demonstrated it to be a valid tool in nondemented populations and people with MCI making it an appropriate tool for the MAS study (Nyunt et al, 2009; Acosta Quiroz et al, 2021). Inclusion criteria at baseline were English proficiency sufficient to complete psychometric assessments and self-report questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations